Respuesta :
5x = x^2 + 4
x^2 - 5x + 4 = 0
(x - 4)(x - 1) = 0
x = 4, 1
(x + 6)^2 = 100
x + 6 = +/1 sqrt100
x + 6 = +/- 10
x = 4, -16
x^2 - 5x + 4 = 0
(x - 4)(x - 1) = 0
x = 4, 1
(x + 6)^2 = 100
x + 6 = +/1 sqrt100
x + 6 = +/- 10
x = 4, -16
Moving everything to one side:
x^2 - 5x + 4 = 0
Factor:
(x-4)(x-1)
x = 1, 4
--------------------------------
Take the square root of both sides:
[tex]x+6=\pm \sqrt{100} [/tex]
[tex]x = \pm10 - 6[/tex]
x = -16, 4
x^2 - 5x + 4 = 0
Factor:
(x-4)(x-1)
x = 1, 4
--------------------------------
Take the square root of both sides:
[tex]x+6=\pm \sqrt{100} [/tex]
[tex]x = \pm10 - 6[/tex]
x = -16, 4